RANKINGS AS A TOOL FOR MONITORING THE QUALITY OF HIGHER EDUCATION - BEBKO, Svitlana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
The article studies the quality of higher education and rankings as a tool of monitoring the quality of higher education. Special attention is dedicated to the methodological approaches to understanding the quality of higher education. There has been proved that today the ranking systems have become widely distributed and applied in the world and European educational space. There has been researched different approaches to classifying the most significant international and Ukrainian rankings, their demands and indicators. There has been studied that the ranking assessment of the activities of higher education institutions of all forms of ownership is an integral part of international and national monitoring of higher education.